BASED ON THE WORKS OF IMAM AL-BUKHARI, ELEMENTARY SCHOOL STUDENTS DEVELOP ASENSE OF NATIONAL PRIDE - Shabdullayeva Lazokatxon Orifbekovna; Nishonboyev Omatillo Ravshanbek o`g`li (Zeta Repository, 2023)
In this article, the rich spiritual heritage of our country's hypocrites is the universal importance of the spiritual heritage of Imam al-Buxorah, a great writer, and scholar, as well as the morality of developing a sense of national pride in the development of nationalism among elementary school students, the ownership of discipline is widely stated.